2007
DOI: 10.1197/j.aem.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Emergency Medicine Resident Training in Informed Consent for Procedures

Abstract: Objectives: To determine emergency medicine (EM) residents' perceptions and reported practices of obtaining informed consent for emergency department procedures. Methods:The authors performed a cross-sectional observational study of EM residents. A brief, shortanswer survey was distributed that covered the following topics related to informed consent: training, confidence and comfort levels, and current practices. Data were analyzed using basic frequency displays, and descriptive statistics are reported.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…According to a study, 78% of residents are not fully aware of the risks, benefits, and alternatives of procedures, and feel uneasy about getting consent from patients. (14) This lack of information on the residents' part, will relate to the lack of information for the patients, and is believed to show a correlation with patients' satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, 78% of residents are not fully aware of the risks, benefits, and alternatives of procedures, and feel uneasy about getting consent from patients. (14) This lack of information on the residents' part, will relate to the lack of information for the patients, and is believed to show a correlation with patients' satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Chirurgische Fächer, allen voran Orthopädie und Unfallchirurgie, sind besonders exponiert, wenn es um Behandlungsfehler und Regressansprüche von Patienten geht [ 4 , 5 ]. Obwohl dabei als wichtiger und direkt beeinflussbarer Faktor die umfassende und regelrechte, d. h. gesetzeskonforme, präoperative Aufklärung des Patienten identifiziert wurde [ 4 ], wird diese häufig von Assistenzärzten niedrigen Ausbildungsstandes durchgeführt [ 3 ], ohne dass zuvor eine systematische Schulung dazu stattgefunden hätte [ 9 , 16 , 18 ]. Auch die wirtschaftlichen Implikationen im Falle geltend gemachter Regressansprüche aufgrund fehlerhaft geführter Aufklärungsgespräche können ein Argument sein, angehenden Ärztinnen und Ärzten früh entsprechende Informationen mit auf den Weg zu geben.…”
Section: Diskussionunclassified
“…In a study by Gaeta et al, 6 involving 16 residency programs, 56% of emergency medicine residents reported no formal training in obtaining IC and 56% reported feeling uncomfortable obtaining IC. Few residents felt very confident that they could provide comprehensive information to patients.…”
Section: Introductionmentioning
confidence: 99%
“…Residents' confidence in obtaining IC increased upon completion of an educational program that included didactic, roleplay, and patient simulation elements. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%